PERLINDUNGAN HUKUM BAGI TENAGA MEDIS DALAM MELAKUKAN TINDAKAN MEDIS TERKAIT DENGAN PEREDARAN OBAT DAN VAKSIN PALSU - I Gede Perdana Yoga (Fakultas Hukum Universitas Dwijendra, 2019)
ABSTRACTThe practice of counterfeiting drugs or vaccines can occur on patent medicinal products or generic drugs with various counterfeiting criteria such as brand forgery, without containing active substances, reduced levels of active substances, different active substances, counterfeit packaging so that it looks the same as the original drug but the quality is very different.The type of research that the authors use in this study is a type of normative legal research that is looking at and analyzing from the standpoint of legislation and prevailing norms specifically related to the problems in this study. From the discussion and analysis above, it can be concluded that the protection of doctors in terms of performing medical actions related to the circulation of fake vaccines to protect doctors from all lawsuits in conducting medical actions, is preventatively regulated in Article 50 of Act Number 29 in 2004 concerning Medical Practice, Article 27 (1) and Article 29 of Law Number 36 of 2009 concerning Health, Article 57 and Article 78 of Law Number 36 of 2014 concerning Health Workers. If in the case of fake vaccines the doctor is only limited as a user and does not know, it means that the doctor is only a victim and is not subject to sanctions. Unless the doctor is proven and knows the vaccine given to patients or injected is a fake vaccine or as an agent, dealers, fake vaccine makers will be held a code of ethics hearing, in the IDI organization there is a forum that serves to protect members from legal issues namely law firms and protection member.Keywords: Health Services, Drug and Vaccine Counterfeiting, Legal Protection